Creating Student Well Being in A Time of Pandemic in Children's Schools - Fauzi Muharom; Mirroh Fikriyati (Program Studi Pendidikan Islam Institut Pesantren KH Abdul Chalim Mojokerto, 2022)
This study aimed to determine the Karima Cita children's School in creating student well-being in the pandemic period. The study subjects were the head of Karima Cita children's School and the children's school teacher Karima Cita. The data collection techniques in this study use interviews and document studies. Data analysis techniques are data reduction, presentation of data, and conclusions. The result of the study is that the strategy of creating Student well-being in Karima Cita children's School in the pandemic period is first by inviting children to introduce new themes through the zoom meeting application or google meet. Second, make a small study group from house to house or home visit while still doing health protocols. Third by preparing and providing a variety of learning with tools and materials. Fourth, create an activity sheet or module for home. Student well-being that wants to be achieved from the above strategies include children more prosocial to all friends and teachers, children get psychological welfare such as more spirit or more optimistic, happier, feel involved in learning activities and get more satisfaction in the learning experience, children will feel cared for by their teachers, children can be creative independently, and children have resilience in the face of learning achievement problems.